Gerakan Progresif Muhammadiyah Dalam Pembaharuan Pendidikan Islam Dan Sosial Keagamaan Di Indonesia - Muhammad Sholeh Marsudi; Zayadi Zayadi (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
This paper aims to discuss the progressive movement of Muhammadiyah in the renewal of Islamic and socio-religious education in Indonesia, which includes the history of Muhammadiyah as a progressive movement, renewal of Islamic education in Muhammadiyah and Muhammadiyah as a socio-religious movement. The method used is library research and analyzed with a reflective thinking approach by combining deductive and inductive approaches. The results of the discussion show that Muhammadiyah as a progressive Islamic movement was driven by the awareness of social responsibility at the time of its birth through the modernization of education and social activism. Muhammadiyah education reform movement. Muhammadiyah's educational modernization by adopting a secular educational institutional system and modernizing the Islamic education system in madrasas/Islamic boarding schools. In the social and religious fields, Muhammadiyah's businesses and activities are realized through various Muhammadiyah charities. Keywords: Muhammadiyah; Educational Reform; Religious Social Abstrak : Tulisan ini bertujuan untuk membahas tentang gerakan progresif Muhammadiyah dalam pembaharuan pendidikan islam dan sosial keagamaan di Indonesia, yang mencakup sejarah Muhammadiyah sebagai gerakan progresif, pembaharuan pendidikan islam di Muhammadiyah dan Muhammadiyah sebagai gerakan sosial keagamaan. Metode yang digunakan adalah library resarch dan dianalisis dengan pendekatan reflektif thinking dengan memadukan pendekatan deduktif dan induktif. Hasil pembahasan menunjukan bahwa Muhammadiyah sebagai gerakan progresif Islam didorong oleh kesadaran tanggung jawab sosial pada masa kelahirannya melalui modernisasi pendidikan dan aktivisme sosial. gerakan pembaharuan pendidikan Muhammadiyah. Modernisasi pendidikan yang dilakukan Muhammadiyah dengan mengadopsi sistem kelembagaan pendidikan sekuler dan modernisasi sistem pendidikan islam di madrasah/pesantren. Di bidang sosial dan keagamaan usaha dan kegiatan Muhammadiyah diwujudkan melalui berbagai amal usaha Muhammadiyah. Kata kunci: Muhammadiyah; Pembaharuan Pendidikan; Sosial Keagamaan